Chirped optical soliton propagation in birefringent fibers modeled by coupled Fokas-Lenells system. (February 2022) - Triki, Houria; Zhou, Qin; Liu, Wenjun; Biswas, Anjan; Moraru, Luminita; Yıldırım, Yakup; Alshehri, Hashim M.; Belic, Milivoj R.
Highlights: The propagation of ultrashort light pulses in a birefringent optical fiber is studied. The spatiotemporal dispersion, cross- and self-phase modulation, self-steepening, and group-velocity dispersion effects are considered. The chirped solitons for the system including the dark-dark and bright-bright soliton pairs in the presence of all fiber parameters are retrieved. Abstract: The propagation of ultrashort light pulses in a birefringent optical fiber exhibiting spatiotemporal dispersion, cross- and self-phase modulation, self-steepening, and group-velocity dispersion effects is addressed. The evolution of light pulses in such system is described by the coupled Fokas-Lenells equations which offer an accurate description of pulse dynamics in the femtosecond range when certain terms of the next asymptotic order beyond those necessary for the nonlinear Schrödinger equation are sustained. We report the first analytical demonstration of the propagation of chirped solitons in a birefringent fiber medium governed by the coupled Fokas-Lenells equations. The formation of those nonlinearly chirped solitons in the optical material may be attributed to the presence of self-steepening process. The results show that the frequency chirp associated with each of the two field components is directly proportional to the total intensity of the pulse. The chirped solitons for the system including the dark-dark and bright-bright soliton pairs in the presence of all fiber parameters are retrieved. The chirps accompanying the soliton pairs are also determined. The existence constraints of these chirped solitons are presented. In addition, the stability of the chirped solutions with respect to the finite perturbations is studied numerically.